Hydrogen as a Co-electron Donor for Chain Elongation With Complex Communities - Baleeiro, Flávio C. F.; Kleinsteuber, Sabine; Sträuber, Heike (Frontiers in Bioengineering and Biotechnology, 2021)
Electron donor scarcity is seen as one of the major issues limiting economic production of medium-chain carboxylates from waste streams. Previous studies suggest that co-fermentation of hydrogen in microbial communities that realize chain elongation relieves this limitation. To better understand how hydrogen co-feeding can support chain elongation, we enriched three different microbial communities from anaerobic reactors (A, B and C with ascending levels of diversity) for their ability to produce medium-chain carboxylates from conventional electron donors (lactate or ethanol) or from hydrogen. In the presence of abundant acetate and CO2, the effects of different abiotic parameters (pH values in acidic to neutral range, initial acetate concentration, and presence of chemical methanogenesis inhibitors) were tested along with the enrichment. The presence of hydrogen facilitated production of butyrate by all communities and improved production of i-butyrate and caproate by the two most diverse communities (B and C), accompanied by consumption of acetate, hydrogen, and lactate/ethanol (when available). Under optimal conditions, hydrogen increased the selectivity of conventional electron donors to caproate from 0.23 ± 0.01 mol e-/mol e- to 0.67 ± 0.15 mol e-/mol e- with a peak caproate concentration of 4.0 g L-1. As a trade-off, the best-performing communities also showed hydrogenotrophic methanogenesis activity by Methanobacterium even at high concentrations of undissociated acetic acid of 2.9 g L-1 and at low pH of 4.8. According to 16S rRNA amplicon sequencing, the suspected caproate producers were assigned to the family Anaerovoracaceae (Peptostreptococcales) and the genera Megasphaera (99.8% similarity to M. elsdenii), Caproiciproducens, and Clostridium sensu stricto 12 (97%-100% similarity to C. luticellarii). Non-methanogenic hydrogen consumption correlated to the abundance of Clostridium sensu stricto 12 taxa (p<0.01). If a robust methanogenesis inhibition strategy can be found, hydrogen co-feeding along with conventional electron donors can greatly improve selectivity to caproate in complex communities. The lessons learned can help design continuous hydrogen-aided chain elongation bioprocesses.